“Black Parade” Song: How Beyonce Criticized Racism - Muzayyanah Awaliyah; Mutmainnah Mustofa; Iklila Ummu Sam'ah (INTERACTION: Jurnal Pendidikan Bahasa, 2021)
From time to time, the communication media in order to propose social criticism which is expected to provide better changes are increasingly diverse. One of them is through the delivery of messages in the lyrics of a song. Beyonce is one of the artist who often uses song as a media to propose her social criticism. In the case of the death of George Floyd a black American, murdered by the white Minesotta police (white supremacist) he released an album with one of the song in it entitled "Black Parade" to convey her response to this case. This research aims to reveal the meaning contained in the lyrics of the song. In order to find this meaning, the researchers use a qualitative approach to the type of document studies. There are three findings of meaning implied in the lyrics of this song, there are self-confidence, social criticism (racism) and race emancipation.